PENGUATAN KUALITAS SPIRITUAL LANSIA MELALUI KEGIATAN SHOLAWAT DI UPT PELAYANAN SOSIAL TRESNA WERDHA BANYUWANGI - Wahyu Efendi; Maftukhah Khoirun Nissa Rozi; Nafi’atus Salma SW; Soffy Balgies (Mukaddimah: Jurnal Studi Islam, 2022)
This study aims to improve and strengthen the spirituality of the elderly at UPT Tresna Werdha Social Services Banyuwangi. Problems faced related to the spiritual quality of the elderly include; First, there is no special spiritual guidance, especially in studies with the theme of prayer for the elderly because religious activities only focus on the science of monotheism. Second, the elderly are not used to practicing prayers every day. Third, the elderly have not been able to improve and strengthen spiritually so that there is anxiety in the elderly. This study uses a CBR (Community Based Research) approach which is qualitatively carried out. The CBR method is a research method with the community to address existing problems. Researchers used two activities as a tool to improve and strengthen the Spiritual Quality of the Elderly. The first activity is a religious activity with the theme "recitation and reading of sholawat". The second activity is the screening of Sholawat every morning.The results of the activities carried out by researchers are that this research activity has succeeded in strengthening the spirituality of the elderly. This is evidenced by the fact that the elderly are very enthusiastic, conducive and participate in "recitation and prayer readings" activities and are also consistent in reading prayers every day. Keyword: Eldery Spiritual, Social Service, Religious, Sholawat